(untitled) (World Marxist Review, 2024)
In recent years, the concept of the “Global South” has emerged as a pivotal issue impacting the international community, shedding light on new shifts and trends in the power dynamics between Northern and Southern nations in the context of great changes unseen in a century. Since the global expansion of capitalism, Western value systems and knowledge paradigms have long exerted dominance over the international landscape and the trajectory of human civilization, serving as historical constraints that hinder independent development, secure interaction and cultural integration in the “Global South.” As the world is undergoing a process of multi-polarization and with a collective awakening of the “Global South,” this widely representative group bears a historic mission to establish its own knowledge system, chart an independent course of development, and reshape international political and economic orders. China naturally aligns with the Global South since its modernization efforts and global initiatives offer wisdom and strength for achieving independent development, shared security and a civilized vision. Inspired by an uplifting vision of building a community of shared future for humanity, China stands ready to collaborate closely with the “Global South” in redefining the trajectory of human civilization while ushering in a new era where civilizations harmoniously coexist.